2006
DOI: 10.1097/00042737-200602000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of hepatoprotective peptide adiponectin in non-alcoholic fatty liver disease

Abstract: Serum adiponectin levels are significantly lower in NAFLD patients with elevated liver enzymes. Non-alcoholic steatohepatitis patients show lower levels of adiponectin with higher grades of inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 35 publications
3
32
1
1
Order By: Relevance
“…The abnormalities in glucose and lipid metabolism and also blood pressure that can potentially affect endothelial function are frequently accompanied by NAFLD [3,27]. Therefore, including only the subjects free from any confounding factor is an important feature of the present investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormalities in glucose and lipid metabolism and also blood pressure that can potentially affect endothelial function are frequently accompanied by NAFLD [3,27]. Therefore, including only the subjects free from any confounding factor is an important feature of the present investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the uncleaved (high molecular weight form) of adiponectin was found to suppress cytokine-induced NF-␤ activation in cardiac fibroblasts and endothelial cells, whereas the proteolytic cleavage product activated NF-␤ and thereby promoted expression of pro-inflammatory and adhesion molecule (Hattori et al, 2007;Tomizawa et al, 2008). Clinical studies revealed that plasma adiponectin levels were lower in patients with nonalcoholic fatty liver disease compared with healthy subjects and were inversely correlated with grade of inflammation and extent of liver injury (Musso et al, 2005;Pagano et al, 2005;Aygun et al, 2006;Targher et al, 2006;Wong et al, 2006). Consequently, replenishing adiponectin levels by its recombinant substitute attenuated steatosis in overnutrition, obesity, and insulin resistance but also ameliorated chronic liver injury induced by ethanol and carbon tetrachloride, suggesting that adiponectin may play a central role in the development of hepatic steatosis and fibrosis (Kamada et al, 2003;Xu et al, 2003).…”
Section: Endocrine Mediators and Signaling Network In Hepatic Steatomentioning
confidence: 99%
“…In human patients with NAFLD, serum adiponectin levels were found to be decreased [24]. The transcriptional factor Forkhead/ winged helix (FOXO1) had been recently associated with NAFLD [25][26][27].…”
mentioning
confidence: 99%